A novel ump demulsifier, nd-20-02 assistedmicrowave technology for separation of crude oil emulsions - Nour, Abdurahman Hamid; Rosli, Mohd Yunus; Nour, Azhary Hamid; Abdelrahman, Ali Hassan; Omer, Manal Suliman; Rushdi, Gaafar (2021)
Traditional ways of breaking emulsion using heat and chemicals are disadvantageous from economic and environmental perspectives. In this invention, the potentials of UMP formulated demulsifier assisted-microwave in demulsification of water-in-crude oil emulsions are investigated. The work began with some characterizations to provide understanding of fundamental issues such as formation, formulation and breaking of emulsions by both chemical and microwave approaches. The aim was to obtain optimized operating condition as well as fundamental understanding of water-in-crude oil stability, upon which further development on demulsification processes could be developed. The results obtained in this invention have exposed the capability of UMP demulsifer assistedmicrowave technology in separation of water-in-crude oil emulsion compared with conventional methods.